Gestión del Cambio en las Organizaciones: efectos sobre la actividad y las personas - Carlos Díaz Canepa (Universidade do Porto, 2016)
Organizations tend to create and hold routines that make their work predictable. Changes in organizations often introduce unexpected effects, increasing uncertainty and operational casuistry, affecting people and their activity. The literature on organizational change favors the analysis of factors underlying the change processes, including the role of purposive activity of members of the organization (agency), however, shortly addresses the effects these changes generate about the specific activity of organizational change. Relevant topics are discussed regarding change processes, and effects they entail on people and their performed activities.